Performance comparison of medium access control schemes for IEEE 802.11 - Ahmed, Lubna; Alam, Mahjabeen; Kabir, Amran (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2012.